2006
DOI: 10.2353/jmoldx.2006.060012
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Ligation-Dependent Probe Amplification

Abstract: Genetic aberrations in tumors are predictive for chemosensitivity and survival. A test is needed that allows simultaneous detection of multiple changes and that is widely applicable in a routine diagnostic setting. Multiplex ligation-dependent probe amplification (MLPA) allows detection of DNA copy number changes of up to 45 loci in one relatively simple, semiquantitative polymerase chain reaction-based assay. To assess the applicability of MLPA, we performed MLPA analysis to detect relevant genetic markers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(48 citation statements)
references
References 31 publications
4
44
0
Order By: Relevance
“…Tests that enable the identification of selected chromosome aberrations by other methods are increasingly common: FISH (fluorescence in situ hybridization), QF-PCR (quantitative fluorescence polymerase chain reaction), and MLPA (multiplex ligation-dependent probe amplification) [20][21][22][23][24][25][26][27][28][29][30][31][32]. These methods, having comparable efficacy and diagnostic reliability, making it possible to diagnose SHOX gene rearrangements [33].…”
Section: Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tests that enable the identification of selected chromosome aberrations by other methods are increasingly common: FISH (fluorescence in situ hybridization), QF-PCR (quantitative fluorescence polymerase chain reaction), and MLPA (multiplex ligation-dependent probe amplification) [20][21][22][23][24][25][26][27][28][29][30][31][32]. These methods, having comparable efficacy and diagnostic reliability, making it possible to diagnose SHOX gene rearrangements [33].…”
Section: Diagnosticsmentioning
confidence: 99%
“…Studies employing comparative genomic hybridisation (CGH) are expensive but also are more often used, allowing for simultaneous evaluation of tens of thousands of sequences. In our conditions, with the results of cytogenetic study, excluding the presence of structural aberrations on the Xp arm, the diagnosis of which could be possible at the level of a single chromosome band, we decided to apply the MLPA technique [20][21][22].…”
Section: Diagnosticsmentioning
confidence: 99%
“…It has been shown that normal DNA contamination reduces the amplitude of cancer-specific copy number variations [58] and thus makes their detection more difficult. A titration experiment showed that 50% contamination with normal cells is the limit at which loss of one allele can be still reliably detected by MLPA [64].…”
Section: Mlpa Analysis Of Dna From Cancer Samplesmentioning
confidence: 99%
“…Although a successful MLPA analysis of paraffin DNA specimens has been reported, difficulties are also recognized [16,49,64]. Success may depend on the amount of DNA that is extracted from the paraffin, fixative used and period of fixation, the age of the block, the degree of contamination with normal cells, and other factors.…”
Section: Mlpa Analysis Of Dna From Cancer Samplesmentioning
confidence: 99%
“…Typically, 125 ng DNA were used for MLPA 3 performed on a robotic thermocycler system (RoboAmp 4200, ALS Jena) using oil seals (LCS, Ventana). MLPA reaction products were examined by capillary gel electrophoresis (ABI GA 3500) and quantified by Coffalyser (MRC Holland).…”
mentioning
confidence: 99%